“A Progress that Threatens All Life”: Nature vs. Nurture in Duncan Williamson’s “Mary and the Seal” - Kaličanin, Milena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The paper first discusses two documentaries by Donna Read, Signs Out of Time (2004) and Goddess Remembered (1989), that focus on the pacific tradition of the female centered settlements on the territories of modern Eastern Europe in the Neolithic and Bronze Ages. Read depicts significant findings of a world-renowned archeologist Marija Gimbutas who claims that a peaceful image of Old Europe embodied in the omnipotent Great Mother changed radically towards the end of the third millennium when violent Indo-European nomads came from Russia and shattered the matriarchal utopia of equality and natural harmony. These tribes introduced the principles of hierarchy and violent male-rule. Read’s and Gimbutas’ findings are further developed and examined in the studies by Riana Eisler and Erich Fromm who also claim that conspicuous material aggrandizement of patriarchal culture severely damaged a blissful matriarchal bond between man and nature. These theoretical insights are applied to Williamson’s comprehension of nature vs. nurture issue in “Mary and the Seal” (1997). In portraying a tender relationship between Mary and the seal, as well as its tragic and totally unnecessary shooting, contemporary patriarchal culture is brought to a trial. The mere existence of the bond between Mary and the seal, an embodiment of an idyllic matriarchal unity between man and nature, testifies to the prevalent need for the return to its substantial but long-forgotten values. The theoretical insights of Graves, Althusser, Freire, Fiske and Miller will also be used in the interpretation of the story.
Keywords: nature; nurture; matriarchy; patriarchy; progress; civilization